Nurturing and Parenting: Dual Role of Parent on the Child Development and Socialization - Hidayati, Laily (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga Yogyakarta, 2016)
Many culture believe that parenting begins with birth, but the mother begins raising and nurturing a child well before birth. In the world of child development and socialization, there are two terms that have close meaning and interconnected. Two of the term is